2020
DOI: 10.3393/ac.2020.05.14.2
|View full text |Cite
|
Sign up to set email alerts
|

How to Prevent Anastomotic Leak in Colorectal Surgery? A Systematic Review

Abstract: Anastomosis leakage (AL) after colorectal surgery is an embarrassing problem. It is associated with poor consequence. This review aims to summarize published evidence on prevention of AL after colorectal surgery and provide recommendations according to the Oxford Centre for Evidence-Based Medicine. We conducted bibliographic research on January 15, 2020, of PubMed, Cochrane Library, Embase, Scopus, and Google Scholar. We retained meta-analysis, reviews, and randomized clinical trials. We concluded that mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 63 publications
1
14
0
4
Order By: Relevance
“…Postoperative COVID-19 infection was significantly associated with mortality (adjusted odds ratio, 16.90; P < 0.001), which required surgeons to undertake stringent mitigation measures [ 27 ]. Furthermore, the leakage rate presented in this study was comparable to those of around 10% reported in the pre-pandemic era [ 37 38 ]. In addition, a further study reported a 10-fold increase in mortality among symptomatic COVID-19 patients but only a 2-fold increase in asymptomatic patients after gastrointestinal surgery.…”
Section: Resultssupporting
confidence: 84%
“…Postoperative COVID-19 infection was significantly associated with mortality (adjusted odds ratio, 16.90; P < 0.001), which required surgeons to undertake stringent mitigation measures [ 27 ]. Furthermore, the leakage rate presented in this study was comparable to those of around 10% reported in the pre-pandemic era [ 37 38 ]. In addition, a further study reported a 10-fold increase in mortality among symptomatic COVID-19 patients but only a 2-fold increase in asymptomatic patients after gastrointestinal surgery.…”
Section: Resultssupporting
confidence: 84%
“…The amount of opioid consumption was similar between the two groups (37.5 ± 28.4 mg versus 40.2 ± 25 mg, P = 0.15), and the mean VAS scores did not differ at any time at rest and effort. Concerning the postoperative rehabilitation, there was no difference between the groups: incidence of vomiting and nausea (p = 0.58), length of hospital stay (4 [ [3] , [4] , [5] ] versus 4 [ 4 , 5 ], P = 0.73) and time to recovery of intestinal function.…”
Section: Resultsmentioning
confidence: 95%
“…Total morphine consumption was 12 mg in the WIG arm versus 9 mg. There was no significant difference in hospital stay length with a median of 4 [ [3] , [4] , [5] ] days and postoperative complications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations